2000
DOI: 10.1074/jbc.m002472200
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of Nuclear Receptor Corepressor and Coactivator to the Retinoic Acid Receptor by Retinoid Ligands

Abstract: Ligand activation of retinoic acid receptors (RARs) involves coordinated changes in their interaction with coregulatory molecules. Binding of the agonist all-transretinoic acid to the RAR results in increased interaction with coactivator molecules as well as a decreased interaction with corepressor molecules. Thus, an all-transretinoic acid antagonist might function either by preventing agonist induction of such events or, additionally, by actively increasing repression via corepressor recruitment. We demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
40
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 49 publications
6
40
0
Order By: Relevance
“…The RA functions through RARα and RXR receptors, which act as ligand-inducible transcription factors, and interact with specific DNA targets as heterodimers (RAR-RXR) or homodimers (RXR-RXR) [40][41][42]. We have confirmed previously published observation [24] that treatment with RA enhances IL-3 or GM-SCF-induced differentiation of wt EML cells into CFU-GM progenitors (Fig.…”
Section: Treatment With Retinoic Acid (Ra) Further Attenuates Myeloidsupporting
confidence: 89%
“…The RA functions through RARα and RXR receptors, which act as ligand-inducible transcription factors, and interact with specific DNA targets as heterodimers (RAR-RXR) or homodimers (RXR-RXR) [40][41][42]. We have confirmed previously published observation [24] that treatment with RA enhances IL-3 or GM-SCF-induced differentiation of wt EML cells into CFU-GM progenitors (Fig.…”
Section: Treatment With Retinoic Acid (Ra) Further Attenuates Myeloidsupporting
confidence: 89%
“…In addition, the POU factor Pit-1 interacts with the coactivator CBP/p300, which is itself recruited by SRC-1 (59). Furthermore, it was recently reported that a DNA-dependent retinoic acid receptor/retinoid X receptor interaction increases SRC-1 recruitment in a ligand-dependent manner (60). This study also demonstrated that retinoic acid receptor binding to a DR5 retinoic acid response element facilitates recruitment of the corepressor N-CoR in coimmunoprecipitation assays.…”
Section: Binding To Dna Enhances Interaction Of Ar But Not Grsupporting
confidence: 69%
“…These molecular events further highlight the reversed transcriptional properties of CAR, as ligand for classical receptors performs the exact opposite function, i.e., corepressor displacement and coactivator recruitment. It is interesting that corepressors were initially identified for their ability to repress basal transcription in unliganded or antagonist-occupied receptors (26). Subsequent studies demonstrated that certain estrogen receptor antagonists could recruit corepressors without significantly lowering basal transcriptional activity (24,29,44).…”
Section: Discussionmentioning
confidence: 99%